ANALISIS FAKTOR-FAKTOR KEPUASAN PELANGGAN PADA CV ELZAYN COMMUNICATION - Erick Ivan Gian; Ida Bagus Alit Ksama Putra; Yunyun Ratna H; Siti Nuraeni; Risna Haryati; Putri Dwi Novrina; I Putu Ajie Windu Kertayoga (Universitas Nurtanio Bandung, 2023)
This study aims to examine the effect of: (1) product quality on customer satisfaction, (2) service quality on customer satisfaction, (3) price on customer satisfaction. The research design used in this study is a causal quantitative research. In this study, the research subjects were customers at CV Elzayn Communication and the objects of research were service quality, price and customer satisfaction. The sample in this study amounted to 105 customers. Data were collected by interviews, document recording and questionnaire methods, then analyzed by multiple regression analysis. The results showed that: (1) product quality had a significant effect on customer satisfaction, (2) service quality had a significant effect on customer satisfaction, (3) price had a significant effect on customer satisfaction.